Testosterone and Voluntary Exercise, Alone or Together Increase Cardiac Activation of AKT and ERK1/2 in Diabetic Rats - Chodari,Leila (2016)
Abstract Background: Impaired angiogenesis in cardiac tissue is a major complication of diabetes. Protein kinase B (AKT) and extracellular signal regulated kinase (ERK) signaling pathways play important role during capillary-like network formation in angiogenesis process. Objectives: To determine the effects of testosterone and voluntary exercise on levels of vascularity, phosphorylated Akt (P- AKT) and phosphorylated ERK (P-ERK) in heart tissue of diabetic and castrated diabetic rats. Methods: Type I diabetes was induced by i.p injection of 50 mg/kg of streptozotocin in animals. After 42 days of treatment with testosterone (2mg/kg/day) or voluntary exercise alone or in combination, heart tissue samples were collected and used for histological evaluation and determination of P-AKT and P-ERK levels by ELISA method. Results: Our results showed that either testosterone or exercise increased capillarity, P-AKT, and P-ERK levels in the heart of diabetic rats. Treatment of diabetic rats with testosterone and exercise had a synergistic effect on capillarity, P-AKT, and P-ERK levels in heart. Furthermore, in the castrated diabetes group, capillarity, P-AKT, and P-ERK levels significantly decreased in the heart, whereas either testosterone treatment or exercise training reversed these effects. Also, simultaneous treatment of castrated diabetic rats with testosterone and exercise had an additive effect on P-AKT and P-ERK levels. Conclusion: Our findings suggest that testosterone and exercise alone or together can increase angiogenesis in the heart of diabetic and castrated diabetic rats. The proangiogenesis effects of testosterone and exercise are associated with the enhanced activation of AKT and ERK1/2 in heart tissue.